Operative approach to a case of perineal laceration in an Arabian mare - Yılmaz, Öznur; Şafak, Tarık; Kılınç, Mehmet Akif; Yüksel, Burak Fatih; Ercan, Kerem; Rişvanlı, Ali (Kastamonu Üniversitesi, 2023)
In this report, a case of perineal laceration of a purebred Arabian breed of 5 years old brought to the Clinic of Obstetrics and Gynecology, Faculty of Veterinary Medicine, Firat University was presented. As a result of the examination, it was determined that the lips of the vulva were intact, and the rupture was shaped in the perineal region above the rectum, anus, and vulva as distinct from the rectovaginal laceration after the parturition in mares. For the treatment of the animal, perineoplasty was performed on three different dates, but the targeted success could not be achieved because the rectovaginal fistula was formed.
Keywords: Veterinary Surgery; Veteriner Cerrahi; Veterinary Obstetrics and Gynecology; Veteriner Doğum ve Jinekoloji